Pannexins in ischemia-induced neurodegeneration - Bargiotas, Panagiotis; Krenz, Antje; Hormuzdi, Sheriar G.; Ridder, Dirk A.; Herb, Anne; Barakat, Waleed; Penuela, Silvia; Engelhardt, Jakob von; Monyer, Hannah; Schwaninger, Markus (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Pannexin 1 (Px1, Panx1) and pannexin 2 (Px2, Panx2) form large-pore nonselective channels in the plasma membrane of cells and were suggested to play a role in the pathophysiology of cerebral ischemia. To directly test a potential contribution of pannexins in ischemia-related mechanisms, we performed experiments in Px1−/−, Px2−/−, and Px1−/−Px2−/− knockout mice. IL-1β release, channel function in astrocytes, and cortical spreading depolarization were not altered in Px1−/−Px2−/− mice, indicating that, in contrast to previous concepts, these processes occur normally in the absence of pannexin channels. However, ischemia-induced dye release from cortical neurons was lower, indicating that channel function in Px1−/−Px2−/− neurons was impaired. Furthermore, Px1−/−Px2−/− mice had a better functional outcome and smaller infarcts than wild-type mice when subjected to ischemic stroke. In conclusion, our data demonstrate that Px1 and Px2 underlie channel function in neurons and contribute to ischemic brain damage.
Gesehen am 17.02.2022